Highly Stretchable Separator Membrane for Deformable Energy‐Storage Devices. Issue 23 (21st June 2018) - Shin, Myoungsoo; Song, Woo‐Jin; Son, Hye Bin; Yoo, Seungmin; Kim, Sungho; Song, Gyujin; Choi, Nam‐Soon; Park, Soojin
Abstract: With the emergence of stretchable electronic devices, there is growing interest in the development of deformable power accessories that can power them. To date, various approaches have been reported for replacing rigid components of typical batteries with elastic materials. Little attention, however, has been paid to stretchable separator membranes that can not only prevent internal short circuit but also provide an ionic conducting pathway between electrodes under extreme physical deformation. Herein, a poly(styrene‐ b ‐butadiene‐ b ‐styrene) (SBS) block copolymer–based stretchable separator membrane is fabricated by the nonsolvent‐induced phase separation (NIPS). The diversity of mechanical properties and porous structures can be obtained by using different polymer concentrations and tuning the affinity among major components of NIPS. The stretchable separator membrane exhibits a high stretchability of around 270% strain and porous structure having porosity of 61%. Thus, its potential application as a stretchable separator membrane for deformable energy devices is demonstrated by applying to organic/aqueous electrolyte–based rechargeable lithium‐ion batteries. As a result, these batteries manifest good cycle life and stable capacity retention even under a stretching condition of 100%, without compromising the battery's performance. Abstract : Nonsolvent‐induced phase separation (NIPS) is demonstrated as a promising strategy to fabricate the stretchable separator membrane with high stretchability (270%) and porosity (61%) for both organic‐ and aqueous electrolyte–based deformable energy‐storage devices. Stable cycle retention and sufficient power supply capability are observed even under 100% strain.